The Great critics : an anthology of literary criticism - 4 0 16; 1903-;1906-1968. Smith, James Harry,;Parks, Edd Winfield; 5 (New York : Norton, 1932)
Part 1 contains critical literature from Aristotle to Matthew Arnold. Part 2 contains works of lesser importance but expands on the first section.
Bibliography: p. 921-933.
Keywords: 2 -- 0; 6; History and criticism.;History and criticism. -- Literature;Criticism.;Literature;Criticism.; 20; 2